2015
DOI: 10.1002/adma.201501884
|View full text |Cite
|
Sign up to set email alerts
|

Designing Efficient Solar‐Driven Hydrogen Evolution Photocathodes Using Semitransparent MoQxCly (Q = S, Se) Catalysts on Si Micropyramids

Abstract: Silicon micropyramids with n(+) pp(+) junctions are demonstrated to be efficient absorbers for integrated solar-driven hydrogen production systems enabling significant improvements in both photocurrent and onset potential. When conformally coated with MoSx Cly , a catalyst that has excellent catalytic activity and high optical transparency, the highest photocurrent density for Si-based photocathodes with earth-abundant catalysts is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 44 publications
2
91
0
Order By: Relevance
“…19 In two other cases, the research groups of Loo and Yang independently reported the integration of MoS 2 with silicon nanowire electrodes: an onset potential of +0.25 V (vs. RHE) for SiNW@MoS 2 in 1.0 M Na 2 SO 4 buffer (pH 5.0); +0.3 V (vs. RHE) for MoS 2 /TiO 2 /n + p-Si NW in 0.5 M H 2 SO 4 . 24 And although MoS 2 seems to t the requirement of a HER catalyst, all the deposition methods such as sputtering, sulfurization, and CVD present limitations in terms of economy, safety and performance. 22 The as-grown MoS 2 (2H-MoS 2 ) prepared by chemical vapor deposition was converted to metallic MoS 2 (1T-MoS 2 ) by chemical exfoliation with n-BuLi.…”
Section: Introductionmentioning
confidence: 99%
“…19 In two other cases, the research groups of Loo and Yang independently reported the integration of MoS 2 with silicon nanowire electrodes: an onset potential of +0.25 V (vs. RHE) for SiNW@MoS 2 in 1.0 M Na 2 SO 4 buffer (pH 5.0); +0.3 V (vs. RHE) for MoS 2 /TiO 2 /n + p-Si NW in 0.5 M H 2 SO 4 . 24 And although MoS 2 seems to t the requirement of a HER catalyst, all the deposition methods such as sputtering, sulfurization, and CVD present limitations in terms of economy, safety and performance. 22 The as-grown MoS 2 (2H-MoS 2 ) prepared by chemical vapor deposition was converted to metallic MoS 2 (1T-MoS 2 ) by chemical exfoliation with n-BuLi.…”
Section: Introductionmentioning
confidence: 99%
“…Beside NiO [77,78,89] and Cu 2 O [90], other oxides [91][92][93] were studied as photocathodes for HER, e.g., the mixed oxides p-CaFe 2 O 4 [94] and p-LaFeO 3 with the latter system having presented an interesting value of hydrogen formation rate (11.5 mmol¨h´1) [95]. Metal sulfide photocathodes like CoS [96], CoS 2 [97,98] [99]), nitrides of semi-and non-metallic atoms (GaN [112] and C 3 N 4 [113]), borides of metals (Co 2 B [114]), arsenides of semi-metallic atoms or non-metals (GaPNAs [115], GaAs [116], AlGaAs [116]), tellurides of metals (CdTe QD [73]), and carbides of semi-metallic atoms (4H-SiC [117], 3C-SiC [118]). From the thermodynamic standpoint photoactivated HER can take place provided that p-type photoelectrodes have a small bandgap with respect to the energy separation of water splitting levels, and the lower edge of CB is above the energy level of H + reduction (Figures 16 and 17) [98,119].…”
Section: Photoelectrodes Of P-type For Non Fossil Fuel (H 2 ) Productionmentioning
confidence: 99%
“…Results of the photoelectrochemical performance achieved with PECs utilizing RGO-based photocathodes are reported in Table 4. Finally, we report now on the photoelectrocatalytic activity of p-Si based photocathodes for HER when silicon has different morphologies (nanowires, micropyramidal, nanomesh), various degree of doping (p-, n + and n + pp + ), and diverse types of photoelectrocatalyst (metallic, p-type semiconducting, metal alloy) [63,97,99,111,[125][126][127][128][129][130][131][132][133][134][135][136][137]. A scheme of the energy levels involved in the interface p-Si/electrolyte for HER is given in Figure 19 [126].…”
Section: Photoelectrodes Of P-type For Non Fossil Fuel (H 2 ) Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo-electrochemical devices (PEC) for water splitting applications have stirred great interest, and different approach has been explored to improve the efficiency of these devices and to avoid optical losses at the interfaces with water. These include engineering materials and nanostructuring the device's surfaces [1]- [2]. Despite the promising initial results, there are still many drawbacks that needs to be overcome to reach large scale production with optimized performances [3].…”
mentioning
confidence: 99%